Kesehatan Mental Perspektif Abu Zaid Al-Balkhi dan Implikasinya terhadap Pendidikan Karakter di Era Digital - Muhammad Abdul Rahman Hakim; Nasirudin Nasirudin; Lutfiyah Lutfiyah (Universitas Negeri Padang, 2026)
Mental health is the cornerstone of developing a well-rounded and high-quality character, especially in the digital age, which is marked by social media pressure, instant gratification expectations, and identity crises. This study aims to analyze the thoughts of Sheikh Abu Zaid al-Balkhi in his book Maṣāliḥ al-Abdān wa al-Anfus (The Well-being of the Body and Soul) and to examine its implications for character education in the digital age. This study employs a descriptive qualitative approach based on library research, with content and discourse analysis of primary texts and contextual data. The findings reveal that al-Balkhi divides mental health into preventive and curative functions, grounded in the balance between physical aspects (al-abdān), spiritual aspects (al-anfus), rationality, and spirituality. The implications of these findings in humanistic-oriented education encourage the development of empathetic, resilient, and reflective character, as indicated by Maslow's basic needs such as safety, love, self-esteem, and self-actualization. Meanwhile, in a holistic approach, al-Balkhi's thinking aligns with Miller's emphasis on integrative character education, encompassing cognitive, affective, psychomotor, and spiritual aspects, thereby producing intellectually and emotionally balanced character. Indicators include emotional management skills, moral stability, healthy social relationships, and spiritual reflection. The conclusion of this study affirms that al-Balkhi's ideas are highly relevant as a foundation for character education in the digital age, blending classical Islamic approaches and modern psychological theories within a humanistic, holistic educational framework.